Keeping up with the US: Why Europe's productivity is falling behind - Fredrik Erixon; Oscar Guinea; Oscar du Roy (European Centre for International Political Economy (ECIPE), 2024)
The European Union stands at a crossroads. For decades, the EU's productivity growth has consistently lagged the United States, leading to slower growth in living standards and decline in global economic power. While short-term factors like the strong US fiscal expansion have widened the gap in nominal GDP growth in recent years, the fact is that Europe has trailed the US economic development for several decades and the root of the problem lies in deeper structural issues within the European economy.
Keywords: 330